Applying the zeros switch-off technique to reduce static energy in data caches - Ubal, R.; Sahuquillo, J.; Petit, S.; Lopez, P. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2006)
Zeros switch-off is a leakage energy reduction technique applicable to cache memories. It works at the cache word level by removing the power supply of all or part of its most significant bytes when they store a zero, taking advantage of the high percentage of zero data bits in common programs. Experimental results, obtained by using the SPEC2000 benchmarks suite, show that the average leakage energy savings reach 60.3% with no IPC loss indeed. The proposed technique can be combined with other existing energy reduction techniques, reaching, on average, 67.3% savings with 0.5% IPC losses